Comparative proteomic analysis of Ulva prolifera response to high temperature stress - Fan, Meihua (Proteome Sci, 2018)
BACKGROUND: Ulva prolifera belongs to green macroalgae and is the dominant species of green tide. It is distributed worldwide and is therefore subject to high-temperature stress during the growth process. However, the adaptation mechanisms of the response of U. prolifera to high temperatures have not been clearly investigated yet. METHODS: In this study, isobaric tags for relative and absolute quantitation (iTRAQ) labelling was applied in combination with the liquid chromatography-tandem mass spectrometry (LC-MS/MS) to conduct comparative proteomic analysis of the response of U. prolifera to high-temperature stress and to elucidate the involvement of this response in adaptation mechanisms. Differentially expressed proteins (DEPs) of U. prolifera under high temperature (denote UpHT) compared with the control (UpC) were identified. Bioinformatic analyses including GO analysis, pathway analysis, and pathway enrichment analysis was performed to analyse the key metabolic pathways that underlie the thermal tolerance mechanism through protein networks. Quantitative real-time PCR and western blot were performed to validate selected proteins. RESULTS: In the present study, 1223 DEPs were identified under high temperature compared with the control, which included 790 up-regulated and 433 down-regulated proteins. The high-temperature stimulus mainly induced the expression of glutathione S-transferase, heat shock protein, ascorbate peroxidase, manganese superoxide dismutase, ubiquitin-related protein, lhcSR, rubisco activase, serine/threonine protein kinase 2, adenylate kinase, Ca(2+)-dependent protein kinase (CDPK), disease resistance protein EDS1, metacaspase type II, NDPK2a, 26S proteasome regulatory subunit, ubiquinone oxidoreductase, ATP synthase subunit, SnRK2s, and cytochrome P450. The down-regulated proteins were photosynthesis-related proteins, glutathione reductase, catalase-peroxidase, thioredoxin, thioredoxin peroxidase, PP2C, and carbon fixation-related proteins. Furthermore, biological index analysis indicated that protein content and SOD activity decreased; the value of Fv/Fm dropped to the lowest point after culture for 96 h. However, APX activity and MDA content increased under high temperature. CONCLUSION: The present study implied an increase in proteins that were associated with the stress response, oxidative phosphorylation, the cytokinin signal transduction pathway, the abscisic acid signal transduction pathway, and the glutathione metabolism pathway. Proteins that were associated with photosynthesis, carbon fixation in photosynthesis organisms, and the photosynthesis antenna protein pathway were decreased. These pathways played a pivotal role in high temperature regulation. These novel proteins provide a good starting point for further research into their functions using genetic or other approaches. These findings significantly improve the understanding of the molecular mechanisms involved in the tolerance of algae to high-temperature stress. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12953-018-0145-5) contains supplementary material, which is available to authorized users.